Relevance of inducible nitric oxide synthase for immune control of Mycobacterium avium subspecies paratuberculosis infection in mice. Issue 1 (1st January 2020) - Abdissa, Ketema; Ruangkiattikul, Nanthapon; Ahrend, Wiebke; Nerlich, Andreas; Beineke, Andreas; Laarmann, Kristin; Janze, Nina; Lobermeyer, Ulrike; Suwandi, Abdulhadi; Falk, Christine; Schleicher, Ulrike; Bogdan, Christian; et al.
ABSTRACT: Mycobacterium avium: subspecies paratuberculosis (MAP) causes Johne's disease (JD), an incurable chronic intestinal bowel disease in ruminants. JD occurs worldwide and causes enormous economic burden in dairy industry. Research on JD pathobiology is hampered by its complexity which cannot completely be mimicked by small animal models. As a model the mouse allows dissecting some pathogenicity features of MAP. However, for unknown reasons MAP exhibits reduced growth in granulomas of infected mice compared to other Mycobacterium avium subspecies. Here, we characterized immune reactions of MAP-infected C57BL/6 mice. After infection, mice appeared fully immunocompetent. A strong antigen-specific T cell response was elicited indicated by IFNγ production of splenic T cells re-stimulated with MAP antigens. Function of splenic dendritic cells and proliferation of adoptively transferred antigen-specific CD4 + T cells was unaltered. Isolated splenic myeloid cells from infected mice revealed that MAP resides in CD11b + macrophages. Importantly, sorted CD11b + CD11c − cells expressed high level of type 2 nitric oxide synthase (NOS2) but only low levels of pro- and anti-inflammatory cytokines. Correspondingly, MAP-infected MAC2 expressing myeloid cells in spleen and liver granuloma displayed strong expression of NOS2. In livers of infected Nos2 −/− mice higher bacterial loads, more granuloma and larger areas of tissue damage were observed 5 weeks post infection compared to wild type mice. In vitro, MAP was sensitive to NO released by a NO-donor. Thus, a strong T cell response and concomitant NOS2/NO activity appears to control MAP infection, but allows development of chronicity and pathogen persistence. A similar mechanism might explain persistence of MAP in ruminants.